The Factors of Performance Effectiveness of The Government’s Paddy and Rice Purchase Price Policy in Sawit Boyolali - Tuti, Suni; Suharto, Didik Gunawan; Haryanti, Rina Herlina (Universitas Muhammadiyah Surakarta, 2018)
Research on the factors of performance effectiveness of the goverment’s paddy dan rice purchase price policy in Sawit Boyolali is qualitative research that discusses about the policy of measured success based on performance use 3 variables i.e. encouragement and coercion at the federal level, the capacity of the central/state, and encouragement and coercion at the level of the centre and the regions. The model used to measure the effectiveness of the performance of paddy and rice HPP in Sawit Boyolali is Goggin et al Model. This policy according to researcher has clear goals and objectives. Implementors have the concept that is formulated in the form of the policy drawn up in detail. But the success of these policies need to be well understood by farmers. Researchers assessed the policy for the moment not too relevant to the conditions in the market. Paddy or rice HPP are below the market price. However, the increase in paddy or rice HPP will cause price increase paddy and rice on the market. So we are need to study more in depth. This research become more interesting with the discussion about the goverment’s paddy dan rice purchase price policy in Sawit Boyolali uses central dan vertical model with weaknesses and advantages.